Kinases as Novel Therapeutic Targets in Asthma and Chronic Obstructive Pulmonary Disease - Barnes,PJ (Pharmacological Reviews, 2016)
Multiple kinases play a critical role in orchestrating the chronic inflammation and structural changes in the respiratory tract of patients with asthma and chronic obstructive pulmonary disease (COPD). Kinases activate signaling pathways that lead to contraction of airway smooth muscle and release of inflammatory mediators (such as cytokines, chemokines, growth factors) as well as cell migration, activation, and proliferation. For this reason there has been great interest in the development of kinase inhibitors as anti-inflammatory therapies, particular where corticosteroids are less effective, as in severe asthma and COPD. However, it has proven difficult to develop selective kinase inhibitors that are both effective and safe after oral administration and this has led to a search for inhaled kinase inhibitors, which would reduce systemic exposure. Although many kinases have been implicated in inflammation and remodeling of airway disease, very few classes of drug have reached the stage of clinical studies in these diseases. The most promising drugs are p38 MAP kinases, isoenzyme-selective PI3-kinases, Janus-activated kinases, and Syk-kinases, and inhaled formulations of these drugs are now in development. There has also been interest in developing inhibitors that block more than one kinase, because these drugs may be more effective and with less risk of losing efficacy with time. No kinase inhibitors are yet on the market for the treatment of airway diseases, but as kinase inhibitors are improved from other therapeutic areas there is hope that these drugs may eventually prove useful in treating refractory asthma and COPD.